2014
DOI: 10.2166/wp.2014.105
|View full text |Cite
|
Sign up to set email alerts
|

The transformative effect of the introduction of water volumetric billing in a disadvantaged housing area in Sweden

Abstract: Domestic water payment schemes are often a product of their time, place and what is perceived to be customary. Aspects that payment schemes can take into account include resource conservation, equity, maintainability, and profitability. In contemporary Sweden profitable environmentally sustainable solutions are promoted, such as the introduction of volumetric billing of water in rental apartments. This paper describes the detailed consequences of this change in the payment structure for domestic water in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In Sweden, the real estate owner pays the heating cost. In the past decades, individual volumetric metering billing of electricity and water have been increasingly installed in rental apartments in Gothenburg [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, the real estate owner pays the heating cost. In the past decades, individual volumetric metering billing of electricity and water have been increasingly installed in rental apartments in Gothenburg [40].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the heat exits the building in the waste water [41]. Excluding heating for water usage from energy performance, which is most strongly predicted by living area per person [33,40], is one manner of separating the impact of user behavior. When excluding energy for heating domestic hot water, no significant association between energy performance and building ownership could be made.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for reduced energy use through behavioural change has been estimated at 10-25% [83]. Regarding energy use for domestic hot water, individualisation of metering and billing has shown promising yet varying results [84]; however, it has also been found that low-income households experience significant cost increases from this measure as household size, i.e., the number of residents in the household that use hot water for e.g., showering, tends to be greater among low-income earners [85]. More so, increased time at home due to e.g., unemployment or illness will further increase water use among the worst-off [85].…”
Section: More Energy-efficient Behaviourmentioning
confidence: 99%
“…This observation further reinforces the recommendation [9] to make a plausibility check and remove outliers. Water usage can vary greatly between dwellings with fewer residents [33], but in larger buildings a more constant water usage, best predicted by the number of residents, can be assumed [34]. The author recommends values below 10 kWh/m 2 year for hot water heating to be removed as outliers for multi-familydwellings.…”
Section: Household Electricity and Watermentioning
confidence: 99%